Factor Of Brand Loyalty In Sportswear Among Student Athletes - Pa, Wan Ahmad Munsif Wan; Zainal, Mohd Syazwan; Mahmud, Muhammad Sofwan (The journal of contemporary issues in business and government, 2021)
Sportswear is now a major and relevant debate among student athletes as it suits their unsophisticated lifestyle, versatility and ease. Brand loyalty is regular purchases of possessions or amenities or other beneficial habits in marketing, such as word of mouth. Therefore it is vital for the sportswear company to determine and monitor the factor of brand loyalty among their consumer. The objective of this study is to examine the factor of brand loyalty such as brand name, product quality, price, style, store environment, promotion and services quality that influences choice of sportswear among student athletes in term of gender. There were were 108 student athletes form Universiti Teknologi Mara (Perlis campus) willing to participate in this study. The study design selected in this study was survey research design, quantitatively. Researcher has used the Statistical Package for the Social Sciences (SPSS), version 23, to evaluate inferential statistics of Independent T- Test. The result of this study report that there was a significant difference of promotion factor between gender. Moreover, male student athletes were highly influenced by promotion factor compare to female student athletes. In conclusion, the researcher found that promotion was the prominent factor of brand loyalty among male student athletes in Universiti Teknologi Mara, UiTM (Perlis campus).